DEVELOPMENT STRATEGY FOR VILLAGE ENTERPRISE (BUMDES) USING SWOT ANALYSIS IN CIHIDEUNG ILIR VILLAGE - Agustina, Nina; Andria, Ferdisar; Wihartika, Doni; Syafaat, Fitra (Yayasan Education and Social Center, 2024)
This research, conducted in Cihideung Ilir Village, Ciampea District, Bogor Regency, at Ngahiji Village-Owned Enterprise (BUMDes) in June 2022, unveils the exceptional resource potential of BUMDes Ngahiji. While the enterprise currently requires assistance in understanding business planning and financial management, its potential for growth and development is undeniable. The research aims to not only analyze the potential of BUMDes Ngahiji but also to identify internal and external factors that affect its development and map alternative business strategies that it can employ. The methods used are SWOT analysis. The results of this research are expected to be a beacon of hope, serving as an essential reference in managing and promoting village potential, and supporting economic development and community empowerment and institutions